PENINGKATAN EFEKTIVITAS PEMBELAJARAN LARUTAN PENYANGGA MELALUI PENDEKATAN SAVI (Somatis, Auditori, Visual, dan Intelektual) PADA SISWA KELAS XI SMAN 21 JAKARTA - Arieztania Rahmadhani; Irma Ratna Kartika; Muktiningsih Nurjayadi (Jurnal Riset Pendidikan Kimia (JRPK), 2013)
The purpose of this research was to increase learning effectiveness of buffer solution through SAVI (Somatic, Auditory, Visual, and Intellectual) approach using experiment guide and CD in class XI SMAN 21 Jakarta. It started from December 2011 until April 2012. The method was classroom action research in two rounds. This research started with preliminary analysis by teacher interview and student questionnaire to make the lesson plan. The results showed that the learning effectiveness had enhancement from first cycle to second cycle. It could be seen from the average of learning outcomes that increased from 73,89 in first round to 81,28 in second round. To increase learning effectiveness of buffer solution through SAVI approach, first we could know the dominant learning style of student in that class and the characteristic of subject that learnt. After that, teacher could determine learning method and media that suited with them. Application of experiment guide and CD as implememtation of SAVI approach could optimized visual and auditory learning style of student. Besides that, experiment in the laboratory could optimized somatic learning style of student. Keywords : effectiveness, SAVI approach, buffer solution